2021
DOI: 10.14218/jcth.2021.00173
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Metabolic-associated Fatty Liver Disease

Abstract: The diagnosis of metabolic-associated fatty liver disease is based on the detection of liver steatosis together with the presence of metabolic dysfunction. According to this new definition, the diagnosis of metabolic-associated fatty liver disease is independent of the amount of alcohol consumed. Actually, alcohol and its metabolites have various effects on metabolicassociated abnormalities during the process of alcohol metabolism. Studies have shown improved metabolic function in light to moderate alcohol dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 131 publications
(176 reference statements)
0
11
0
Order By: Relevance
“…104,106 The precise mechanisms underlying the synergism between alcohol and metabolic dysfunction remain elusive. However, they might involve combined effects on mitochondrial dysfunction, oxidative stress, [107][108][109] CYP2E1 activity, 110 innate immune response activation, 111 hepatic stellate cell activation, 112 gut microbiota and increased gut permeability, 113,114 bile acid metabolism (e.g., farnesoid X receptor and fibroblast growth factor 21), 115,116 lipid metabolism, 117 and adipocyte dysfunction with subsequent increases in lipolysis and proinflammatory factor release. 118 Mouse studies have demonstrated that moderate obesity and alcohol use can synergistically induce steatohepatitis and liver fibrosis.…”
Section: Potential Mechanisms Of Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…104,106 The precise mechanisms underlying the synergism between alcohol and metabolic dysfunction remain elusive. However, they might involve combined effects on mitochondrial dysfunction, oxidative stress, [107][108][109] CYP2E1 activity, 110 innate immune response activation, 111 hepatic stellate cell activation, 112 gut microbiota and increased gut permeability, 113,114 bile acid metabolism (e.g., farnesoid X receptor and fibroblast growth factor 21), 115,116 lipid metabolism, 117 and adipocyte dysfunction with subsequent increases in lipolysis and proinflammatory factor release. 118 Mouse studies have demonstrated that moderate obesity and alcohol use can synergistically induce steatohepatitis and liver fibrosis.…”
Section: Potential Mechanisms Of Interactionmentioning
confidence: 99%
“…Moreover, alcohol is an energy-dense molecule and can therefore induce metabolic dysfunction and contribute to obesity through caloric excess. 117 One gram of ethanol is nearly as energy dense as one gram of dietary fat.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The high prevalence of MAFLD among employed adults may be explained by night shift work, which could increase the risk of developing both obesity [15] and abnormal liver function [31]. Another reason may be explained by the high prevalence of unhealthy lifestyles such as smoking and drinking, which may lead to MAFLD [6,7]. In this study, most participants were male (96.2%), among which high smoking rate and alcohol consumption existed.…”
Section: Discussionmentioning
confidence: 73%
“…A prediction of future years is on the rise, making China the country with the fastest growing MAFLD population worldwide [4]. MAFLD is not just a liver disease but one component of a multi-faceted, multiorgan collection of metabolic dysfunctions [5], driven by the complex interaction between genetic factors [2] and lifestyle behaviors (e.g., smoking and alcohol abuse) [6,7]. Primordial prevention, such as leading a healthy lifestyle, is promising to reduce the risk of MAFLD [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The rebranding of NAFLD to MAFLD reinforces the contribution of excessive alcohol intake to the disease etiology. One of the primary effects of chronic heavy alcohol consumption (>60 g of pure alcohol on one occasion [ 154 ] for more than five years) or binge drinking (>40 g for women and >50 g for men within two hours) is the elevated risk of obesity attributed to its high caloric content (generating 7.1 kcal per gram of ethanol), leading to a higher BMI and WC, and is found to have a stronger link in men at different ages than in women [ 155 ]. The pathophysiology of alcohol-induced liver diseases closely resembles that of NAFLD, despite the term nonalcoholic implying a distinct etiology [ 156 ].…”
Section: Pathogenesis Of Mafldmentioning
confidence: 99%